Energy, Exergy, Exergoeconomic, and environmental (4E) analyses of thermal power plants for municipal solid waste to energy application in Bangladesh. (October 2021) - Adnan, Adib; Mahmud, Shadman; Uddin, Mohammed Raihan; Modi, Anish; Ehsan, M. Monjurul; Salehin, Sayedus
Highlights: Approximately 250 MW of power can be recovered from waste in Bangladesh. A detailed thermoeconomic model based on incineration technology is presented. Exergoeconomic analysis shows plant cost is affected more by operational costs. COE of proposed plant is 53.9 USD/MWh, comparable to existing power plants. Proposed plants have better environmental efficiencies than coal, oil power plants. Abstract: With a population of 165 million, Bangladesh is undergoing rapid industrialization and urban development, and is well on track to move out from the group of least developed countries by 2024. This results in a significant increase in the urban energy needs and the amount of generated waste. Most of the municipal solid waste in Bangladesh is currently deposited in landfills, thereby contaminating nearby cultivable soils. It is desirable to have a system that recovers energy from the municipal solid waste in order to satisfy the increasing energy needs, while simultaneously addressing the land scarcity and pollution issues. This paper proposes using incineration to recover energy from municipal solid waste to produce electricity in the urban areas of Dhaka and Chattogram. A detailed technical analysis involving energy, exergy, exergoeconomic, and emission is presented. The power plants in these two cities show potential capacities of 169 MW and 83 MW respectively, with exergoeconomic factors of 61 %. The results indicate energy and exergy efficiencies of 32 % and 27 %, respectively, and a production cost in the range of 53.9–56.7 USD/MWh which is comparable to the production cost from the current power plants in Bangladesh. The proposed plants also result in a reduction in the greenhouse emissions and exhibit ecological efficiencies of over 87 %.